Den jødiske forbindelse. En ny vurdering af Theodor Herzl og zionismens tilknytning til jødisk kultur i 1800-tallet - Feldt, Jakob Egholm; Simonsen, Cecilie Speggers Schrøder (Historisk Tidsskrift, 2015)
The Jewish Connection A new Assessment of Theodor Herzl’s and Zionism’s Attachment to Jewish Culture in the 1800s This article shows how the founder of political Zionism, Theodor Herzl, was much more a product of Jewish cultural trends in the 1800s than canonical and biographical Zionist literature generally acknowledges him to be. Since the publication of the earliest Zionist biographies in the early 1900’s and until recently, scholars have emphasised Herzl’s German and modernist cultural identity and environment—not his Jewishness. In this article we demonstrate how Herzl’s works and political and cultural visions unfolded within knowledge resources developed since the 1820s within the Jewish community by European Jewish urban intellectuals such as Heinrich Heine and Meïr Aron Goldschmidt and others. We conclude that Herzl’s Zionism was less of a revolution in Jewish history than scholarly literature generally credits it with being.